FORMATION OF STUDENTS’ ENVIRONMENTAL COMPETENCE IN THE CONTEXT OF SOCIO-CULTURAL INITIATIVE - Vizniuk, Inessa; Dolynnyi, Serhii; Dolynna, Anna (Personality and environmental issues, 2025)
The article considers the process of forming students' environmental competence as a key component of their professional training in the context of socio-cultural initiatives. The relationship between environmental awareness and socio-cultural activities is analyzed, and the criteria and levels of environmental competence are determined. The author's program for developing students' environmental awareness is presented, based on problem-based learning, an interdisciplinary approach, and the integration of environmental knowledge into the socio-cultural context. The effectiveness of the program is studied through experimental testing, which confirmed its impact on the formation of a responsible attitude towards the environment, an ecological worldview, and active participation of students in sustainable development. The article considers environmental competence as an integrative formation that ensures the ability of students to effectively solve environmental problems in socio-cultural contexts. The relationship between environmental competence and the knowledge, skills, values, and social responsibility necessary for participation in sustainable development and environmental protection activities is determined. The role of teachers in the implementation of environmental practices and the formation of a responsible attitude towards the environment is outlined. An ecological worldview as a component of professional activity emphasizes the importance of integrating environmental principles into professional practice. Experimental work confirmed the effectiveness of the program for the development of students' environmental awareness, based on problem-based learning, simulation modeling and the case method. The program contributes to the formation of an ecological worldview and professional readiness of future specialists, provides knowledge, skills and values for environmental activities. The integration of environmental education into all levels of education forms a responsible attitude towards the environment, critical thinking and civic activity, contributing to the sustainable development of society.